2013
DOI: 10.4236/jbise.2013.62022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary CoQ<sub>10</sub> and α-lipoic acid on CoQ<sub>10</sub> levels in plasma and tissues of eggs laying hens

Abstract: In this paper we described the effect of administrated CoQ 10 , and alfa-lipoic acid on the concentration of total CoQ 10 in plasma end body tissues of eggs laying hens. Organisms raise a complex network of enzymes, metabolites and molecules with antioxidant activities in order to prevent oxidative damage of theirs bodies. Adequate blood concentrations of small weight molecules ingested with food and food additives are important for the proper functioning of the antioxidant defense. To test this hypothesis we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Observations on the measurement of serum enzyme activity of selected antioxidant enzymes in this experiment are consistent with the recent hypothesis (Table 5). This experiment has also shown that the increase in CoQ10 plasma concentrations in young chickens is greater than in adult hens during the supplementation with CoQ10 [37].…”
Section: Discussionmentioning
confidence: 99%
“…Observations on the measurement of serum enzyme activity of selected antioxidant enzymes in this experiment are consistent with the recent hypothesis (Table 5). This experiment has also shown that the increase in CoQ10 plasma concentrations in young chickens is greater than in adult hens during the supplementation with CoQ10 [37].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, in thermoneutral birds fed with CoQ 10 at a concentration of 40 mg/kg in the diet, daily CoQ 10 consumption was approximately 10 mg/kg body weight (BW). Calculations using data from another study indicate that the concentration of CoQ 10 in broiler chickens is around 16 mg/kg BW (Krizman et al 2013). These observations suggest that the daily CoQ 10 dose administered in this study is equivalent to approximately 63% of the total CoQ 10 present in a broiler chicken.…”
Section: Discussionmentioning
confidence: 54%
“…Calculations using data from another study indicate that the concentration of CoQ 10 in broiler chickens is around 16 mg/kg BW (Krizman et al . ). These observations suggest that the daily CoQ 10 dose administered in this study is equivalent to approximately 63% of the total CoQ 10 present in a broiler chicken.…”
Section: Discussionmentioning
confidence: 97%
“…특히 생산성 향상을 위 해 고도로 육종된 산란계의 경우 지방간 현상이 빈발하여 간 조직의 산화적 스트레스가 매우 심각하다 (Julian, 2005;Trott et al, 2014;Lin et al, 2021). 따라서 산란계에 CoQ10 을 급여할 경우 체 조직의 미토콘드리아 기능과 항산화 작 용의 증진으로 대사작용으로 발생되는 산화 스트레스부터 신체를 방어하는 중요한 역할을 기대할 수 있다 (Krizman et al, 2013;Jang and Moon, 2016). 육용종계 암탉에서도 CoQ10 급여 시 간 기능 장애와 체 지방을 감소시켜 미토콘 드리아 대사 작용이 활성화되는 것으로 보고되었다 (Sharideh et al, 2020).…”
unclassified